2022
DOI: 10.1155/2022/2633127
|View full text |Cite
|
Sign up to set email alerts
|

The Gender-Specific Interaction of DVL3 and GSK3β Polymorphisms on Major Depressive Disorder Susceptibility in a Chinese Han Population: A Case-Control Study

Abstract: Based on the “oxidative stress hypothesis” of major depressive disorder (MDD), cells regulate their structure through the Wnt pathway. Little is known regarding the interactions of dishevelled 3 (DVL3) and glycogen synthase kinase 3 beta (GSK3β) polymorphisms with MDD. The aim of the current study was to verify the relationship between DVL3 and GSK3β genetic variants in a Chinese Han population and further to evaluate whether these interactions exhibit gender-specificity. A total of 1136 participants, consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…50 In addition, DVL3 is involved in the pathogenesis of MDD in female Chinese Han patients. 32 In agreement with these data, we also found that the cortisol levels of PS2 knock-in mice were higher than those of PS2 WT mice. These results…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…50 In addition, DVL3 is involved in the pathogenesis of MDD in female Chinese Han patients. 32 In agreement with these data, we also found that the cortisol levels of PS2 knock-in mice were higher than those of PS2 WT mice. These results…”
Section: Discussionsupporting
confidence: 89%
“…It was also demonstrated that the mRNA and protein levels of DVL3 in healthy individuals are significantly different from those of depressed individuals 50 . In addition, DVL3 is involved in the pathogenesis of MDD in female Chinese Han patients 32 . In agreement with these data, we also found that the cortisol levels of PS2 knock‐in mice were higher than those of PS2 WT mice.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Variants in the CRHR1 gene have also been shown to have a protective effect on developing depression after childhood trauma among males, but not females [ 54 ]. There was a significant association between disheveled 3 ( DVL3 ) and glycogen synthase kinase 3 beta ( GSK3β ) variants, both involved in the Wnt pathway that is implicated in oxidative stress, and the risk of developing MDD among Chinese Han women [ 55 ]. An additional study found a significant sex-by-SNP interaction on depression for APOE in patients with Alzheimer’s disease such that women with the APOE epsilon4 allele were almost 4 times more likely to have depression than those without the APOE epsilon4 genotype [ 56 ].…”
Section: Candidate Gene Studies Of Depression and Sexmentioning
confidence: 99%